Assessment of training of general practice interns in motivational interviews about vaccination. Issue 6 (30th November 2022) - Mitilian, Eva; Gosselin, Virginie; Casanova, Ludovic; Fressard, Lisa; Berthiaume, Patrick; Verger, Pierre; Gagneur, Arnaud
ABSTRACT: The effectiveness of motivational interviewing (MI) for reducing vaccine hesitancy (VH) has been demonstrated in Quebec. We conducted a study to evaluate the acquisition of MI skills after MI training via videoconferencing for interns training as general practitioners (GPs) in southeastern France. A vaccination-specific MI training workshop was offered to interns in 2021, consisting of two separate Zoom videoconference sessions. Participants completed the Motivational Interviewing Skills in Immunization questionnaire before and after the training to measure skills acquisition. We used pairwise exact Wilcoxon-Pratt signed rank tests for the analysis. Among 45 GP interns enrolled in the first MI session, 34 (75.6%) attended both sessions and completed the questionnaire at 3 different time points. After the first session, MI knowledge scores improved significantly (+21.1 ± 21.6; P  < .0001), as did application of MI skills (+36.8 ± 36.7; P  < .0001), and MI practice confidence (+21.2 ± 11.1; P  < .0001). The second MI session maintained the skills developed after the first session without further improvement. Participant satisfaction was high. This is the first study in France assessing the impact of a vaccination-specific MI training for GP interns. It shows a substantial improvement in knowledge, application of MI skills, and self-confidence in the practice of MI. GP interns were highly satisfied with the training despite the videoconference format. These promising results will allow the integration of MI training in GP medical curricula in order to prepare future GPs for communication in the field of vaccination.